Vitamin D and anti-Müllerian hormone concentration in human follicular fluid individually aspirated from all patient follicles. (2nd January 2022) - Skowrońska, Patrycja; Kunicki, Michał; Pastuszek, Ewa; Konieczna, Lucyna; Bączek, Tomasz; Męczekalski, Błażej; Smolarczyk, Roman; Łukaszuk, Krzysztof
Abstract: Objective: The main aim of this prospective study was to investigate the relationship between intrafollicular vitamin D and anti-Müllerian hormone (AMH) concentration and its impact on oocyte quality and developmental competence. Methods: The analysis was performed on 208 follicular fluid (FF) samples obtained from 33 patients undergoing ovarian stimulation as part of in vitro fertilization (IVF) treatment that included intracytoplasmic sperm injection. Results: Our study shows that vitamin D concentration in FF varies according to the developmental stage of the oocyte and corelates with embryo development status on day 3, while AMH concentration in FF is not correlated with the developmental potential of an oocyte. We demonstrated that the levels of vitamin D and AMH were higher in FF than in serum. Moreover we showed that AMH and vitamin D levels were positively correlated in FF but not in serum. Conclusion: FF-AMH levels do not appear to be a suitable as noninvasive test of the developmental potential of an oocyte, while FF-vitamin D level can be used to evaluate whether embryos obtained from particular oocytes have potential of reaching the third day of culture. However, our results encourage further research to be carried out on a larger number of patients and testing additional components found in FF such as androgens.